Disinfection of zygotic embryos of Ceroxylon alpinum Bonpl. in vitro establishment - Serna-Toro, Estefany; Villa-Ramírez, Rigoberto; Arbeláez-Arias, Lina A. (Agronomía Mesoamericana, 2025)
Introduction. The Ceroxylon genus includes Andean palm species that are vulnerable due to human intervention. Specifically, the seeds of Ceroxylon alpinum Bonpl. exhibit low germination rates, slow growth, and require complex environmental interactions for development. Objective. To evaluate disinfection methods for zygotic palm embryos to enable in vitro culture and micropropagation. Materials and methods. The study was conducted between February 2021 and March 2022. Wax palm (Ceroxylon alpinum Bonpl.) seeds were collected in the El Cairo forest, Salento, Quindío, Colombia, during the fruiting stage, selecting those with good morphological development and phytosanitary conditions. The seeds were then transported to the Plant Biotechnology Laboratory-CIBUQ in Armenia, Quindío. Surface disinfection was performed using neutral detergent Tween 20 at a concentration of 0.1 % (v/v) and running water, followed by immersion in 3 % NaClO for 25 minutes. The embryos were extracted under a stereoscope and immersed in 70% alcohol for one minute. They were then subjected to different NaClO concentrations for 10 minutes before being cultured in MS medium and evaluated for eight weeks. A completely randomized design with a single factor (NaClO concentration) and three levels (1 %, 1.5 %, and 2 %) was used, analyzed through ANOVA and Tukey’s test (α = 0.05) using Statistica 8 software. Results. Disinfection with 1.5 % NaClO (T2) was the most effective, achieving 75 % survival and 74 % embryo sprouting. In contrast, the 2 % NaClO concentration increased contamination. Conclusion. The disinfection method using 1.5 % NaClO was the most effective for enabling the viability of wax palm zygotic embryos, maximizing in vitro survival and sprouting, thereby facilitating micropropagation and the conservation of endangered species.